Intimate Partner Violence Against Older Women: Findings from Austria - Amesberger,Helga (2012)
Research on intimate partner violence (IPV) against older women follows either a gender-specific or an age-specific approach. This paper which summarises the results of research on IPV against older women (defined as 60+) in Austria, shows the importance of an integrated approach, bridging the gap between domestic violence on the one hand and abuse of the elderly on the other. As accounts of older women affected by IPV are rare, this paper focusses on their experiences and perspectives. Furthermore the paper deals with the question to which extent institutions are confronted with IPV, with their characterisations of victims and perpetrators as well as with the help-seeking behaviour of older women and the needs for service improvement.